Deja vu: Medieval Motifs in Modern Arab Political Life - V. V. Naumkin; V. A. Kuznetsov (Vestnik MGIMO-Universiteta)
The article analyzes specific elements of the Arab societies’ political life which distinguish it from political relations in the Western nation-states. Admitting the existence of a large number of such kind of elements, the authors focus only on three of them which are related to the sources of power and its distribution. Emphasizing that these elements are deeply rooted into the Arab-Muslim political tradition, so that they have tended to be present throughout the whole Islamic period of the region, the authors find out that each of them has its own medieval countertype. Thus, the article addresses the dichotomy of the supreme power of caliphs and sultans, formed in the IX – XI centuries and manifested today both in Jihadist organizations (i.e. ISIS, Al-Qaeda) and in the political strategies of moderate Islamist movements, such as Tunisian party Al-Nahda. The second example is the urban militias, which are correlated with the medieval phenomenon of «young hero» or «chivalry» communities – fityan. The fityan communities have seven specific traits, which not only are characteristic of the militias, but also demonstrate fundamental difference between the militias and urban criminal groups. Major attention is paid to Libyan militias, which are studied on the materials of field research conducted by one of the authors. Finally, the third element discussed is the particular role of the army and other security forces in the Arab political systems.The authors provide three possible interpretations of all the revealed coincidences. According to the first one, they are presented as aberrations of the researcher’s scientific consciousness, which make them look for historical equivalents to contemporary issues. Second interpretation belongs to the tradition of «the new medievalism». According to it, the described phenomenon is in fact the revival of some medieval practices, caused by the end of the Modernity era. The last interpretation views the analyzed elements as distinctive civilization traits of the Arab world.